Facies analysis of Sunakothi Formation, Kathmandu basin, Nepal and its significance (Journal of Nepal Geological Society, 2014)
This study decipher facies characteristic of Sunakothi Formation at southern part of Kathmandu Basin. Thick sandy and muddy sequence is found on an open lacustrine facies of the Kalimati Formation. Five facies associations have been recognized within the sandy and muddy facies. These are: (a) muddy rhythmites and silt and laminated to ripple sand bed of the prodeltaic origin (pd), (b) association of cross-stratification, rippledrift and parallel lamination in the lacustrine delta front origin (df), (c) muddy flood-plain and alteration of the fine and coarse sediments of delta-plain origin (dp), (d) sandy to silty rhythmites of the marginal shallow lacustrine origin above the delta-plain (ml), and (e) association of fluvial origin (fl ). Former three associations are interbeded by the thick gravel deposits, which is gravelly braided river origin. Transition from lacustrine to alluvial system is characterized by fluvial and deltaic system in the south. Sedimentology of the Sunakothi Formation indicates deposition during rapid lake level rise and also the thick channelized fluvial gravel beds within the sandy and muddy sequence indicate lake level fall. The cause could be climatic as well as activity of the basin margin tectonics. Sunakothi Formation is the southern counterpart of the Thimi-Gokarna Formations distributed in the northern part of the basin.